Sleep patterns of young children with newly diagnosed atopic dermatitis - Dogan, Derya Gumus; Canaloglu, Sinem Kortay; Kivilcim, Meltem; Kum, Yunus Emre; Topal, Erdem; Catal, Ferhat (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Even though atopic dermatitis (AD) most often begins in the first year of life, it is not well known whether sleep disturbances occur following the onset of the disease or whether they develop later. Aim : To determine the sleep patterns of young children already diagnosed with AD in comparison to a control group by using a validated questionnaire, the Brief Infant Sleep Questionnaire (BISQ). Material and methods: Forty-six children with a new diagnosis of AD and 60 healthy children, aged 3–36 months, participated in the study. Their sleep behaviors were assessed using the BISQ along with a structured sociodemographic data form. Results: It was found that when compared with healthy children, children with AD did not have decreased daily total sleep duration (p = 0.1); however, it was found that they woke up more frequently at night (52.2% vs. 40%, p = 0.4) and they stayed awake significantly longer than 60 min when they woke up (41.3% vs. 11.7%, p < 0.05). In addition, mothers of children with AD reported that their children had three times as many sleep problems compared to the reports of mothers of healthy children. Conclusions : The findings of this study showed that sleep disturbance was more common in young children with already diagnosed AD, and the BISQ provided a practical way to assess the sleep patterns. The use of a screening tool to enable early identification and treatment of childhood sleep problems among patients with AD should be encouraged.